An Investigation of Financial Soundness of Listed Manufacturing Companies in Sri Lanka: an Application of Altman’s Model - Nimalathasan, B. (My University, 2009)
The financial position of listed companies is an issue that every stakeholder is concerned about very much. The management of the companies tries every means to improve the company’s financial position, and hopes to maintain good trends in the future. Investors also pay close attention to companies’ financial position and the investment decisions they make are based on this. The study is about the investigation of financial soundness of listed manufacturing companies for a period of 5 years, i.e. from 2003 to 2007. The test of soundness as revealed by Z score (Altman’s model) showed that the selected companies were on the verge of failure. In order to save the companies from total bankruptcy, their financial position should be improved without any further delay. To this aim, therefore, the necessity of qualified trained and experienced management personnel, government realistic measure, participative management, supply of adequate working capital, setting realistic goals, rectifying the accountability, motivating the achievement of performance and imposing penalty for non-achievement must be ensured in the sample of selected listed companies. Hence, the appropriate authority should take immediate measures for the removal of bankruptcy.
Keywords: financial soundness; Altman’s model; listed manufacturing companies